2015
DOI: 10.1111/jph.12414
|View full text |Cite
|
Sign up to set email alerts
|

Two Endopolygalacturonase Genes in Trichoderma virens: In Silico Characterization and Expression during Interaction with Plants

Abstract: The ability of Trichoderma spp. to antagonize most phytopathogenic fungi\ud and to interact with plants by inducing their resistance and promoting\ud their growth has been widely described. Endopolygalacturonases\ud (endoPGs) produced by Trichoderma spp. can assist root penetration and\ud play a pre-eliciting role in induced systemic resistance (ISR), a beneficial\ud effect detected in plants colonized by Trichoderma. In this study, two\ud endoPG genes (Tvpg1 and Tvpg2) have been identified and partially chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Thus, the expression analyses confirmed a primed response of mycorrhizal plants to the OG treatment under sufficient P (Figures 5A-D; Table S5). A similar primed response was found for the gene encoding a defense polygalacturonase inhibiting protein (LePGIP), also related to defense responses (Baroncelli et al, 2016) (Figure 5E).…”
Section: P Availability Impacts the Levels Of Defense-related Phytoho...supporting
confidence: 69%
“…Thus, the expression analyses confirmed a primed response of mycorrhizal plants to the OG treatment under sufficient P (Figures 5A-D; Table S5). A similar primed response was found for the gene encoding a defense polygalacturonase inhibiting protein (LePGIP), also related to defense responses (Baroncelli et al, 2016) (Figure 5E).…”
Section: P Availability Impacts the Levels Of Defense-related Phytoho...supporting
confidence: 69%
“…A study of T. harzianum-root interaction in Arabidopsis and tomato led to the discovery of the first DAMP, which corresponds to the oligogalactouronides produced by the enzymatic activity of CWDE endopolygalacturonase ThPG1 in T. harzianum, which was found to be capable of inducing systemic defense in the plants ( Moran-Diez et al, 2009). In a study conducted by Baroncelli et al (2016), the expression of two endopolygalcturonase genes (viz., TvPg1 and TvPg2) from T. virens I10 was examined during the interaction with tomato roots. The results revealed that, while interacting with, in particular, host roots or pectin, expression of TvPg1 was induced, whereas TvPg2 was later expressed constitutively.…”
Section: Cell Wall-degrading Enzymesmentioning
confidence: 99%
“…The 16S rRNA gene sequence of B. licheniformis IEB-8 was blasted in the NCBI nucleotide database. The 16S rRNA gene sequence of the first ten strains showed resemblance to the isolate used for the multiple sequence alignment (ClustalW; https://www.genome.jp/tools-bin/clustalw) and for the construction of the phylogenetic tree using Multiple Evolutionary Genetic Analysis (MEGA) (Version 6, https://www.megasoftware.net/download_form) (Baroncelli et al 2016;Khan and Latif 2016).…”
Section: Multiple Sequence Alignment and Phylogenetic Tree Analysismentioning
confidence: 99%